Analisis Faktor Self Care Management Hipertensi pada Pra Lansia Sampai Lansia di Wilayah Terpencil Kepulauan Nias Sumatera Utara - Rina Silviana; Fahmi Ichwansyah; Asnawi Abdullah; Hermansyah Hermansyah; Hafnidar Hafnidar; Amelia Zahara (Malahayati Nursing Journal, 2026)
ABSTRACT Hypertension is a chronic disease that has characteristics in unsTabel bloodpressure, so it needs a long treatment that can even be up to a lifetime and requiresconsiderable medical expenses. Hypertension is a condition in which systolic bloodpressure is equal to or higher than 140 mmHg and diastolic blood pressure is higher than 90 mmHg. This study aimed to analyze the factors associated with hypertension self-care management among pre-elderly and elderly individuals living in remote areas of Nias Regency, North Sumatra. This quantitative study employed a cross-sectional design. Data were collected over one month, from May 30 to June 30, 2024, through face-to-face interviews using a structured questionnaire. The study population comprised all hypertensive patients aged 45–74 years, categorized as pre-elderly and elderly, within the working area of Ehosakhozi Public Health Center. A total of 80 respondents were selected using random sampling. Data were analyzed using cross-sectional analysis with STATA version 14.0. The results showed that 50% of pre-elderly and elderly respondents had poor self-care management. Poor self-care management was predominantly found among the elderly group (75%) compared to the pre-elderly group (25%) (OR = 15.55; 95% CI = 3.29–73.41; p = 0.001). Insufficient family support increased the risk of poor self-care management by nearly four times (OR = 3.74; 95% CI = 1.12–12.51; p = 0.032). Gender, educational level, marital status, smoking history, alcohol consumption, and self-efficacy were also significantly associated with hypertension self-care management. Educational level was identified as the most dominant factor associated with hypertension self-care management among pre-elderly individuals. It is expected that healthcare providers will encourage and assist family members in supporting the care of pre-elderly and elderly individuals with hypertension. Keywords: Hypertension, Pre-elderly, Elderly, Self Care Management   ABSTRAK Hipertensi merupakan penyakit kronis yang memiliki karakteristik pada tekanan darah yang tidak stabil, sehingga perlu dilakukan pengobatan yang lama bahkan bisa sampai seumur hidup dan membutuhkan biaya pengobatan yang cukup besar. Untuk menganalisis faktor Self Care management hipertensi pada pra lansia sampai lansia di wilayah terpencil, Kabupaten Nias Sumatera Utara. Penelitian ini bersifat kuantitatif dengan rancangan Cross-Sectional. Pengumpulan data dilakukan selama sebulan sejak 30 Mei sampai dengan 30 Juni 2024 dengan wawancara langsung menggunakan kuesioner. Populasi dalam penelitian ini ada seluruh pasien yang mengalami hipertensi dari rentan usia 45-74 tahun dengan kategori pra lansia sampai lansia yang berada di wilayah kerja Puskesmas Ehosakhozi. Sampel yang diambil sebanyak 80 orang dengan teknik random sampling dan dianalisis dengan uji Cross-Sectional menggunakan aplikasi STATA 14.0. Hasil penelitian menunjukkan bahwa sebanyak 50% pra lansia dan lansia memiliki Self Care management kurang baik. Pra lansia dan lansia yang memiliki Self Care management kurang baik mayoritas pada kelompok lansia 75% dibandingkan dengan kelompok pra lansia 25% (OR=15,55; 95%CI=3,29-73,41; p=0,001). Dukungan keluarga yang kurang berisiko hampir 4 kali mengalami Self Care management kurang baik (OR=3,74; 95%CI=1,12-12,51; p=0,032). Jenis kelamin, pendidikan, status perkawinan, riwayat merokok, konsumsi alkohol dan Self Efficacy juga berhubungan dengan Self Care management hipertensi. Pendidikan menjadi faktor yang paling dominan berhubungan dengan Self Care management hipertensi pada pra lansia. Diharapkan petugas kesehatan dapat menghimbau dan membantu anggota keluarga untuk dapat merawat pra lansia sampai lansia dengan hipertensi. Kata Kunci: Hipertensi, Pra Lansia, Lansia, Self Care Management.